Enabling Institutional Investors' Collective Action: The Role of the Principles for Responsible Investment Initiative. (March 2013) - Gond, Jean-Pascal; Piani, Valeria
This article analyzes the process of organizing collective action by studying the role of the organizational platform provided by the United Nations–backed Principles for Responsible Investment (PRI) initiative in supporting institutional investors' collaborative engagement with corporations on environmental, social, and governance issues. The authors combine stakeholder and collective action theory to explain how institutional investors influence corporations through collective engagement. A unique access to data from the PRI secretariat on two cases of collaborative campaigns allows evaluation of our framework. The findings clarify how investors enhance their sources of power, legitimacy, and urgency and attract managers' attention through collaborative engagement, and show how they manage these attributes to reshape the legitimacy and urgency of their claims in the eyes of managers. Our data suggest that "enabling organizations" such as the PRI initiative facilitate the emergence of collective action by lowering barriers to entry and providing a mobilizing structure, support collaborative efforts by adding their own legitimacy, normative power, and persistence to the collaborative engagement, and create conditions for a lasting dialogue between investors and managers by providing a hybrid organizational space.